On the Problem of Linear Widths of the Classes $B_{p,θ}^r$ of Periodic Functions of Many Variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish order estimates for the linear widths of the classes $B_{p,θ}^r$ of periodic functions of many variables in the space $L_q$ for some relationships between the parameters $p, q$, and $θ$.